Pengaruh Intensitas Penggunaan YouTube Terhadap Kepuasan Karyawan Dalam Mendapatkan Hiburan yang Diinginkan - Ekohandito, Rahardian Shandy; Luthfiyyah, Annisa (Prisani Cendekia Institute, 2023)
The study investigates how using YouTube affects employee satisfaction in getting desired entertainment. This research uses the descriptive quantitative research method and purposive sampling as the data collection technique by distributed questionnaires. The respondents in this research are 75 head office employees of PT Module Intracs Yasatama who actively use YouTube. The study indicates that using YouTube positively impacts on satisfaction among employees in getting desired entertainment. Moreover, based on the coefficient of determination test, it found that the effect of YouTube usage (X) on employee satisfaction in getting the desired entertainment (Y) is 21,8%. Please note that the types of entertainment that most want on YouTube are comedy and podcasts.